TINJAUAN TERHADAP PELAKSANAAN PENGIKATAN JAMINAN FIDUSIA SEBAGAI JAMINAN UTANG PADA BANK AGRO CABANG PEKANBARU - , Hendra Kumar, Taufiq El Rahman, SH.,Mhum ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of this research is on want to accomplish is to know and understand why the implementation of binding Fiduciary guarantee debt as collateral in the bank, in particular Agro Bank Pekanbaru Branch does not comply with the rule of law that regulation is in effect, to know and understand the end of the binding fiduciary guarantee measures and if the debtor Bank Agro Branch Pekanbaru. This study is juridical empiric, i.e., to obtain an overview of a particular circumstance objectively in terms of implementation of binding fiduciary guarantee as security for the debt in the Bank Branch Agro Pekanbaru. Implementation of a binding fiduciary Bank Agro yet everything works in accordance with the rules of the applicable law, because there is a part of the debtor that has liquid credit (loan money has been credited to the account debtor) but fidusianya is not yet listed on the Fiduciary Office, it is because some things are as follows